Breast Cancer Mortality After Implementation of Organized Population-Based Breast Cancer Screening in Norway. (17th December 2019) - Sebuødegård, Sofie; Botteri, Edoardo; Hofvind, Solveig
Abstract: Background: We estimated breast cancer (BC) mortality reduction associated with invitations to a nationwide population-based screening program and with changes in treatment. Materials and methods: BreastScreen Norway started in 1996 and became nationwide in 2005. It invites women aged 50–69 years to biennial mammographic screening. We retrieved individual-level data for 1 340 333 women from national registries. During 1996–2014 (screening window), women contributed person-years in noninvited and invited periods. We created comparable periods for 1977–1995 (prescreening window) by dividing the follow-up time for each woman into pseudo-noninvited and pseudo-invited periods. We estimated BC mortality for the four periods, using the so-called evaluation model: counting BC deaths in each period for all women diagnosed within the period and counting BC deaths and person-years after screening-age for those diagnosed within screening age. We used a multivariable flexible parametric survival model to estimate hazard ratio (HR) for the effect of invitation and improved treatment. Results: Using the regression approach, we found 5818 BC deaths across 16 533 281 person-years. Invitations to screening reduced BC mortality by 20% (HR = 0.80, 95% confidence interval [CI] = 0.70 to 0.91) among women 50 years and older and by 25% (HR = 0.75, 95% CI = 0.65 to 0.86) among screening-aged women. The treatment effect was 23% (HR = 0.77, 95% CI = 0.65 to 0.92) for women 50 years and older and 17% (HR = 0.83, 95% CI = 0.74 to 0.94) for screening-aged women. Conclusion: We observed a similar reduction in BC mortality associated with invitations to screening and improvements in treatment during 1977–2014, among women 50 years and older.